Iatrogenic ANA: An emerging source of expensive diagnostic confusion. (February 2023) - Ali, Hammad; Buechler, Connor R.; Sanaullah, Oneeb; Lucas, Alexandria; Lohr, Kristine L.
Intravenous immune globulin (IVIg) therapy has been shown to be useful in a multitude of disorders. IVIg is produced from pooled human plasma; therefore, autoantibodies found in the general population are also present in IVIg and transferred to those being transfused. This can prove a particular hazard for screening and diagnostic tests based on autoantibodies. We present a patient who was found to have a positive antinuclear antibody (ANA) titer after multiple IVIg transfusions, resulting in diagnostic confusion and unnecessary workup. A 45-year-old gentleman was diagnosed with atypical CIDP, initiated on a course of IVIg, and sent for inpatient rehabilitation. However, recovery was complicated by multiple readmissions for recurrent weakness, and as part of the workup for other etiologies, an ANA was found to be positive. Sub-serologies and paraneoplastic autoantibody panel were negative. In the absence of clinical symptoms, we recommended continued monitoring and repeat ANA testing 6 months after the last dose of IVIg; as any drug needs 5 half-lives to be eliminated from the body. Clinicians should consider any recent IVIg treatments when evaluating the pre-test probability of detecting an underlying connective tissue disease with ANA screening. Indiscriminate ANA levels in patients recently given IVIg lead to unnecessary and expensive further testing and consultation.